Sustitución parcial del cloruro de sodio por el cloruro de potasio en la elaboración de salchicha de pollo a base de zanahoria (Daucus carota) y zapallo (Cucurbita maxima) - Caballero Noboa, Erick Antonio (2022)
The present project seeks to partially substitute the amount of sodium chloride with potassium chloride present in chicken sausage using different treatments as a base. However, the level of substitution will depend on the product, since it has been reported that potassium chloride imparts a bitter taste to meat products above 40% substitution. For this reason, physical-chemical and acceptability analyses will be carried out to determine if the percentages used in the preparation of chicken sausage affect the physical-chemical and sensory characteristics of the final product, since salt is a necessary ingredient in meat products, as it plays an important role in the acceptability of the final products. By means of a factorial analysis AxBxC whose factors A (partial substitution of NaCl x KCl), B (sources of fiber) and factor C (temperature and storage time). These correspond to 8 treatments with 2 replications in total 16 experimental units. The results obtained will be evaluated in an Infostat statistical program to determine the significant differences of each treatment by means of a Tukey test. Based on the physical-chemical characteristics of the chicken sausage, while the sensory characteristics for the final acceptance of the product were evaluated by means of a tasting panel of 73 inhabitants of the city of Quevedo, where it was determined that T1 (1 % KCl and 1.4 % NaCl + 0.93 % carrot + 10 days of storage + 4 ºC) presented better organoleptic characteristics. As for the physical-chemical characteristics, it was concluded that all treatments are within the permissible range established by INEN 1338:96 for meat products. Thus, the partial substitution of NaCl for KCl does not significantly affect the physicochemical and organoleptic characteristics. Key words: Substitution, sensory, partial